GAYA KOMUNIKASI PELATIH DAN MURID SANGGAR TARI PINCUK DALAM MENINGKATKAN RASA PERCAYA DIRI MENGIKUTI PENTAS SENI - Daffa Saputra, Arigo; Riyanto, Buddy; M Sarungu, Lukas (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
ABSTRACT Communication Communication between trainers and students at the Pincuk Dance Studio shows that students' lack of confidence in facing artistic performances can affect their concentration during practice. Some students feel afraid and anxious when they have to appear in front of many people, which has an impact on their learning process. The purpose of this research is to identify and analyze trainers' communication styles that can increase students' self-confidence in facing art performances. Thisresearch uses the theory of empathic and assertive communication styles, which emphasizes the importance of an open and empathetic relationship between trainers and students to create a conducive learning environment. The research was conducted using a qualitative descriptive method, using interview techniques, observation, to collect data. It is hoped that the research results will provide a deeper understanding of effective communication styles in increasing students' self-confidence in performing arts and training environments. Keywords: Communication Style, Coach, Confidence